Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog - McGugan, Jenna R. (2016)
Poison frogs sequester chemical defenses from arthropod prey, although the details of how arthropod diversity contributes to variation in poison frog toxins remains unclear. We characterized skin alkaloid profiles in the Little Devil poison frog, Oophaga sylvatica (Dendrobatidae), across three populations in northwestern Ecuador. Using gas chromatography/mass spectrometry, we identified histrionicotoxins, 3,5- and 5,8-disubstituted indolizidines, decahydroquinolines, and lehmizidines as the primary alkaloid toxins in these O. sylvatica populations. Frog skin alkaloid composition varied along a geographical gradient following population distribution in a principal component analysis. We also characterized diversity in arthropods isolated from frog stomach contents and confirmed that O. sylvatica specialize on ants and mites. To test the hypothesis that poison frog toxin variability reflects species and chemical diversity in arthropod prey, we (1) used sequencing of cytochrome oxidase 1 to identify individual prey specimens, and (2) used liquid chromatography/mass spectrometry to chemically profile consumed ants and mites. We identified 45 ants and 9 mites in frog stomachs, including several undescribed species. We also showed that chemical profiles of consumed ants and mites cluster by frog population, suggesting different frog populations have access to chemically distinct prey. Finally, by comparing chemical profiles of frog skin and isolated prey items, we traced the arthropod source of four poison frog alkaloids, including 3,5- and 5,8-disubstituted indolizidines and a lehmizidine alkaloid. Together, the data show that toxin variability in O. sylvatica reflects chemical diversity in arthropod prey.